Necroptosis-Related Genes Associated With Immune Activity and Prognosis of Colorectal Cancer - Peng, Xinyi; Xu, Zhili; Guo, Yong; Zhu, Ying (Frontiers in Genetics, 2022)
This study aims at screening out the key necroptosis-related genes in colorectal cancer and elucidating the role of necroptosis-related genes in the immune activity and prognosis of in colorectal cancer. The CRC patients’ data were downloaded from The Cancer Genome Atlas (TCGA). Non-negative matrix factorization method was applied to identify new molecular subgroups. Survival analysis and single sample Gene Set Enrichment Analysis were performed to determinate the differences in the overall survival time and immune status of the subgroups. Prognostic model was constructed on the basis of univariate Cox regression and LASSO analysis. Functional analyses were used to explore the potential mechanisms. Based on prognostic related necroptosis genes, we identify 2 molecular subgroups with significantly different survival. Better prognosis was associated with more active immune infiltration and upregulated expression of immune checkpoints. We screened nine necroptosis related genes as key prognostic genes and established a risk model, which showed a good potential for survival prediction in colorectal cancer. Nomogram assessment showed that the model had high reliability for predicting the prognosis of colorectal cancer patients. High-risk and low-risk group also has different sensitivity to the commonly used drugs in colorectal cancer. Overall, necroptosis related genes were involved in the immune microenvironment of colorectal cancer patient, could be utilized to predict the prognosis of colorectal cancer and develop more individualized treatment.